Phacelia as a Green Manure Crop - Kahramon, Utbosarov; Teshayevna, Negmatova Surayyo (American Journal of Biology and Natural Sciences, 2025)
This paper examines the significance of Phacelia (Phacelia spp.) as a green manure crop. Phacelia is highlighted as a valuable plant due to its role in improving soil fertility, enhancing organic matter content, serving as a nectar source for bees, and providing high-quality fodder for livestock. The study also considers the agronomic, ecological, and phytosanitary benefits of incorporating Phacelia into crop rotation systems, thereby emphasizing its contribution to sustainable agriculture.